Evaluation of Physiological, Haemato-Biochemical Parameters in Tibial Shaft Fracture Repair by Supracutaneous Plating Technique in Cats - Ruchika,; Nagaraja, B N; Mahesh, V; M C, Anilkumar; M H, Girish (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study investigated the variations in physiological and haemato-biochemical parameters during fracture healing in six cats with  tibial shaft fracture, repaired using supra-cutaneous plating technique. During the study period, physiological parameters were recorded  preoperatively and on days 0, 1, 3, 5, 7, 12 and 15 postoperatively, while haemato-biochemical changes were recorded preoperatively  and on days 0, 1, 7, 15, 30, 45 and 60 post-operatively. Physiological parameters showed a significant decrease (p
Keywords: Cat; Haemato-biochemical parameters; Physiological; Supracutaneous plating; Tibial fracture